Structural characterization and magnetic property studies of a mixed-valence CoIIICo II 4 - Fiorini, Guillermo; Carrella, Luca; Rentschler, Eva; Albores, Pablo (Dalton Transactions)
We have synthesized and structurally characterized a new mixed valence pentanuclear Co complex, bearing a rare μ4-O-tetrahedral CoII4 unit, by employing a pyridine-like Schiff base ligand. We have performed DC magnetic susceptibility and magnetization measurements over polycrystalline samples and chemical quantum computations in order to understand the exchange interaction pattern within Co(ii) sites and ground state magnetic anisotropy. This new complex shows an overall antiferromagnetic exchange interaction whose strength strongly depends on the local symmetry of Co(ii) sites. Also, local ion magnetic anisotropy reveals a strongly axial behaviour with the lowest Kramers doublet (KD) at each Co(ii) ion sufficiently isolated from excited states at low temperatures. Two Co(ii) sites show tetrahedral symmetry and the spin only formalism including axial zero-field splitting (ZFS) term properly described them; on the other hand, the other two Co(ii) sites have distorted octahedral and square base pyramidal coordination spheres, and a strong orbital contribution leads to a failure of the spin only formalism. A model of four Seff = 1/2 exchange interacting sites is necessary in order to account for low temperature magnetization behaviour. In view of the strongly anisotropic KD states, the exchange interactions are forced to be modelled as anisotropic ones. Overall, experimental data and quantum chemical computations are in good agreement, supporting the proposed model for magnetic behaviour.
CRIS-Team Scopus Importer:2023-03-27